HUBUNGAN PERKEMBANGAN ANAK USIA TODDLER PADA ANAK YANG LAHIR PREMATUR DAN YANG LAHIR ATERM DI PUSKESMAS UABAU - Brigita Dina Manek (Jurnal Medicare, 2026)
Background: Preterm birth (<37 weeks of gestation) is associated with an increased risk of growth and developmental disorders compared with term birth, making early developmental screening during the golden period essential. Objective: To compare the development of toddlers born preterm and those born at term in the Uabau Primary Health Center working area. Methods: This descriptive comparative field study assessed child development using the Denver Developmental Screening Test (DDST). The sample included 21 toddlers with a history of preterm birth and 30 toddlers born at term, selected through purposive sampling. Data were analyzed using statistical tests with a significance level of 95% (α = 0.05). Results: The analysis showed an Asymp. Sig value of 0.388 (p > 0.05), indicating no significant difference in developmental outcomes between preterm and term-born toddlers. Conclusion: Preterm birth was not associated with significantly different developmental outcomes in this study. Nevertheless, routine developmental monitoring remains important to detect developmental problems early and optimize child development.